Empowering the Migrant and Refugee Family\'s Parenting Skills: A Literature Review - Christiana Kouta; Venetia Sofia Velonaki; Runa Lazzarino; Elena Rousou; Paraskevi Apostolara; AnaMaria Dorou; Victor Dudau; Athena Kalokairinou; Orazio Licciardello; Manuela Mauceri; Elena Nikolaidou; Alfonso Pezzella; et al. (Shahid Sadoughi University of Medical Sciences, 2022)
Bachground: Worldwide, more than 79.5 million people are forcibly displaced, including a significant number of migrant and refugee families with children. Migration and refugeedom affect these families in different dimensions, such as mental, physical and spiritual health. Identifying family needs and enhancing parenting skills can improve family cohesion and health, as well as smooth integration into the host country. This review is part of the Erasmus+ funded project- IENE 8 (Intercultural Education for Nurses in Europe) aiming at empowering migrant and refugee families regarding parenting skills. Methods: This was a scoping review of literature. The IENE 8 partner countries (Cyprus, Germany, Greece, Italy, Romania, and United Kingdom) searched for peer reviewed papers, grey literature and mass media reports at international, European and national level. The time period for the search of scientific and grey literature was between2013-2018, and for mass media, it was between 2016 and 2018. Results: 124 relevant sources were identified. They included 33 Peer reviewed papers, 47 Grey literature documents and 44 mass media reports. This revealed the importance of understanding the needs of migrant families with children. Conclusion: It is evident from the literature that there is a need to support refugee parents to adjust their existing skill and to empower them to develop new ones. Healthcare and social services professionals have an essential role in improving the refugees' parenting skills. This can be done by developing and implementing family-centered and culturally-sensitive intervention programs.